Monitoring Shoreline Evolution on Morocco’s Northern Atlantic Coast Using Remote Sensing and DSAS - Haddaoui, Hatim; Aangri, Abdelhaq; Souiri, Smail; Hakkou, Mounir (Sustainable Marine Structures, 2025)
Coastal zones are dynamic interfaces responding to complex natural processes and anthropogenic pressures. Monitoring shoreline evolution is essential for sustainable coastal management, particularly given climate change, urban expansion, and sediment flux disruption. This study investigates shoreline changes along Morocco's northern Atlantic coast from 1990 to 2023, an area of strategic economic importance and environmental vulnerability. Landsat satellite imagery and geospatial techniques, including the Digital Shoreline Analysis System (DSAS v5.1) and the Normalized Difference Water Index (NDWI), provided a high-resolution, diachronic assessment. Shoreline extraction and image enhancement were conducted with ENVI software, and change detection utilized Linear Regression Rate (LRR) and End Point Rate (EPR) indicators. Results revealed significant spatial variability: sectors like northern Moulay Bousselham and Chlihat showed pronounced accretion (+3.2 to +4.7 m/year), while areas such as Tahaddart and southern Mehdia experienced severe erosion (up to −3.4 m/year). The total net eroded area exceeds 58,000 m². Trends correlate strongly with hydrodynamic forces, upstream damming, sediment extraction, and extreme weather events, notably storms in 2014 and 2017. Findings align with studies highlighting compounded effects of sediment starvation and sea-level rise. By integrating remote sensing, time-series analysis, and uncertainty quantification, this research provides insights into the primary drivers of shoreline dynamics, emphasizing the urgent need for adaptive, evidence-based coastal management strategies, including regulation of sand mining, sediment buffer restoration, and soft-engineering solutions. ER